2001
DOI: 10.1002/cjg2.192
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Research on Anomalous Atmospheric General Circulation in 1998

Abstract: [Abstract] Prediction of climate anomalies and the general atmospheric circulation for the summer of 1998 is studied by using a climate model developed in Japan. Quantitative verification of the accuracy of the prediction was made by applying correlation analysis. Results indicate that the predictive skill is relatively high. Both the SST anomalies and initial atmospheric anomalies in spring are important for causing anomalous rainfall over China and anomalous atmospheric circulation in the Northern Hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Generally, CGCM's uncertainties, which usually result from the nonlinear interaction of the component of the climatic system (Tebaldi et al, 2004;Held et al, 2002), have two types. The first one is due to uncertainty of the physical parameterization (Meehl et al, 2007;Moss and Schneider, 2000;Wittenberg and Anderson, 1998;Dorn et al, 2007), and the other one is from amplification of the computational errors (Cousins and Xue, 2001;Wang et al, 2007;Chen et al, 2008). Those results suggest that uncertain processes or parameterization schemes could cause a quite large uncertainty of the climate simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, CGCM's uncertainties, which usually result from the nonlinear interaction of the component of the climatic system (Tebaldi et al, 2004;Held et al, 2002), have two types. The first one is due to uncertainty of the physical parameterization (Meehl et al, 2007;Moss and Schneider, 2000;Wittenberg and Anderson, 1998;Dorn et al, 2007), and the other one is from amplification of the computational errors (Cousins and Xue, 2001;Wang et al, 2007;Chen et al, 2008). Those results suggest that uncertain processes or parameterization schemes could cause a quite large uncertainty of the climate simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they concluded that the error from the data communication process via MPI is the main reason for the difference. Wang et al (2007) studied the results of the atmospheric model SAMIL simulated with different CPUs and pointed out that the difference is chiefly caused by the round-off error. Chen et al (2008) introduced the uncertainty of the global mean Sea Surface Temperature (SST) simulated by the Community Climate System Model Version 3 (CCSM3) with different computational platforms or different CPU configuration.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform better prediction for the summer rainfall, antecedent signals have been widely sought in the past few years. Studies by Wang et al [2000] and Wang [2001] demonstrated that the summer rainfall in the Yangtze River was largely influenced by the anomalies of the preceding Eurasian atmospheric circulations. It is also documented that Arctic Oscillation and Antarctic Oscillation in spring linked strongly to the summer precipitation in the Yangtze River valley [ Gong et al , 2002; Gong and Ho , 2003; Gao et al , 2003; Xue et al , 2003; Nan and Li , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The results are fairly good among the models of participants in two phase simulations which are 18-month run from April 1997 to September and 10-year run from January 1989 to December 1998 [18,19] . The severe flooding disaster occurred over the Yangtze River Valley and Northeast China in July 1998 [20] . This model reproduced well the main characteristics of the water vapor transport during the heavy rain period [19] .…”
Section: Resultsmentioning
confidence: 99%